Memórias de um imigrante autodidata: de Aveiro à Ribeirão Pires (1891-1978) - Dias, Virginia Nazaré Rocha Aveiro (2006)
Villager Biography or poor life s is the title done for this original material bringing register about his life and experience being this handwork for us used as source and research object. Manoel Olimpio da Rocha Gonçalves, wrote no release intention, maybe for the pleasure of self achievement. Comprehending your world vision, your everyday through of your speech analyze, including revealing the condition of production in your own speech this was our aim. Drawing on studies about everyday, speech analyze and autobiography confessional literature following the line that start to specific from general, coming the maximum possible of world representation in which this sir, person of himself, bellowed